Radiation Effect on MHD Flow of Nanofluids Over an Exponentially Stretching Sheet - Fauzia Raza; A. K. Tiwari (International Journal of Mathematics And its Applications, 2018)
The problem of MHD radiation flow over an exponentially sheet through a porous medium is considered. The consequences of various parameters will be analyzed in Copper (Cu) and Silver (Ag) nanofluid. The non-linear governing equations of flow of thermal fields are converted to ordinary differential equation using similarity transformations and their numerical solution is obtained using MATLAB software ``bvp4c'' under the related boundary conditions. The interesting outcomes for variant physical parameters are exhibited through plots and numerical tables.